Synthesis and properties of crosslinked carboxymethyl chitosan and its hemostatic and wound healing effects on liver injury of rats. (September 2019) - Zhang, Wei; Xin, Yu; Yin, Bin; Ye, Guan L; Wang, Jun X; Shen, Jian F; Li, Lei; Yang, Qi H
Carboxymethyl chitosan has the potential to be used in the field of hemostatic materials, but its low molecular weight and high water solubility limit its application. This study prepared crosslinked carboxymethyl chitosan by crosslinking reaction with glutaraldehyde and determined its physicochemical properties, FT-IR spectra, and toxicity and cell morphology on L929 fibroblasts. The hemostatic effect and healing function of crosslinked carboxymethyl chitosan on rat liver were also evaluated. The animals were divided into three groups ( n  = 18): control group (Con), Surgicel® group (Sur), and crosslinked carboxymethyl chitosan group (C-CMC). The results showed that crosslinked carboxymethyl chitosan with high viscosity was successfully prepared, which had no cytotoxicity and no abnormal effects on cell morphology to L929 fibroblasts of mouse, and had significantly shorter bleeding time and less blood loss compared to Con and Sur ( P  < 0.05). The enzyme activity analysis on 7, 14 and 21 days showed that crosslinked carboxymethyl chitosan can significantly elevate the activities of inflammatory factor enzymes at earlier time and restore them to normal level faster (IL-1β, IL-6, TNF-α, and IFN-γ) ( P  < 0.05). The wound healing effects of crosslinked carboxymethyl chitosan could be reflected by the enzyme activity on rat liver, which can significantly decrease the enzyme activities of ALT and AST ( P  < 0.05) and significantly increase the enzyme activity of VEGF on 7 and 14 days and decreased on 21 days ( P  < 0.05). The crosslinked carboxymethyl chitosan has the potential application of the clinical hemostasis biomaterial, and the present study only conducted a basic research of crosslinked carboxymethyl chitosan, and further investigations should be performed in future.